2017
DOI: 10.1210/js.2017-00305
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat, High-Sugar Diet Disrupts the Preovulatory Hormone Surge and Induces Cystic Ovaries in Cycling Female Rats

Abstract: Diet-induced obesity has been associated with various metabolic and reproductive disorders, including polycystic ovary syndrome. However, the mechanisms by which obesity influences the reproductive system are still not fully known. Studies have suggested that impairments in hormone signaling are associated with the development of symptoms such as acyclicity and ovarian cysts. However, these studies have often failed to address how these hormonal changes arise and how they might contribute to the progression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 135 publications
(125 reference statements)
2
19
2
1
Order By: Relevance
“…On the basis of the relationship between endocrinal alteration and metabolic controls, animal PCOS models using diet are consistent with obese models. A long-term (14 weeks) high-fat and high-sugar diet (HDHS; high fat chow with 60% of the calories derived from fat and 32% sucrose solution as daily water) significantly elevated the serum testosterone and insulin levels in rats [73]. In addition, irregular estrous cycle, increased fat mass, and cystic ovaries were observed.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the relationship between endocrinal alteration and metabolic controls, animal PCOS models using diet are consistent with obese models. A long-term (14 weeks) high-fat and high-sugar diet (HDHS; high fat chow with 60% of the calories derived from fat and 32% sucrose solution as daily water) significantly elevated the serum testosterone and insulin levels in rats [73]. In addition, irregular estrous cycle, increased fat mass, and cystic ovaries were observed.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity, which is defined as a state of having excessive fat tissue that is caused by overnutrition, a sedentary lifestyle, and other environmental factors, is an important risk factor for various metabolic diseases 1 , 2 . Several studies have shown that obesity is closely related to metabolic diseases such as type 2 diabetes, hypertension, and cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since life expectancy of different dog breeds varies, there is a tendency of increasing OC prevalence in dogs over the age of six. A relationship between obesity and OC incidence has been reported in human [ 21 ], mouse [ 27 ], and rat [ 36 ], but investigations into that association in dogs are lacking. Our study population included 38.9% (n = 7/18) overweight bitches, whereas 61.1% (n = 11/18) were normal weighted.…”
Section: Discussionmentioning
confidence: 99%